1049 Are Referrals to Sleep Clinic Necessary Prior to Polysomnography in Children with ADHD?. (27th April 2018) - Hammond, R; Paasch, V; Ewen, J; Lam, J
Abstract: Introduction: Children with ADHD may be difficult to study in the lab due to lack of compliance with the equipment or difficulty adjusting to equipment. Because sleep clinic is an opportunity to provide screening and education regarding PSGs, we hypothesized that patients referred to sleep clinic prior to PSG would have better sleep. Methods: A retrospective chart review was performed on all children with ADHD who completed polysomnography during a one-year period. Data were obtained on referral source, sleep efficiency, sleep latency, wake after sleep onset (WASO), and technician-rated set-up compliance. Analyses included regression modeling and scaled JZS Bayes factor analyses. Results: A total of 69 children were included in this study (22 were female). 34 children were referred to the lab from sleep clinic and 35 children were referred from other clinics. Bayes factor analyses demonstrated that it is more likely than not that referral source (sleep clinic vs. other) has no effect on quality of sleep in the lab, as recorded by sleep latency, sleep efficiency and WASO. The data suggest that it is 3.5 times more likely that there is no effect of referral source on sleep efficiency than an actual effect exists. Bayes factors for a null association between referral source and WASO is 2.2; for referral source and sleep latency, 3.5. Regression analysis yields no significant effect for referral source on technologist-rated set-up difficulty. Regression analysis also failed to show an effect on any parameter, even after controlling for sex and/or age. Conclusion: Our results indicate that referrals from sleep clinic do not impact sleep quality variables compared to referral from other sources. This may indicate that there is no benefit to PSG compliance gained by referral first to the sleep clinic. Thus, a reduction in the wait time and unnecessary medical costs can be avoided by direct referral to the lab. Future studies which compare other populations of children with neurodevelopmental disabilities would provide insight into which patients benefit from the additional education/preparation provided by sleep clinic. Support (If Any): None.